Evaluation of the effectiveness of radio frequency (RF) treatment on improving the overall appearance of the facial skin in women - a pilot study - Monika Wilk; Amelia Lizak; Aleksandra Matuła; Anna Ścisłowska-Czarnecka (University of Applied Sciences in Tarnow, Poland, 2020)
Introduction: Aging facial skin is a natural and unavoidable process. It involves a gradual weakening of the biological activity of cells, extension of regenerative processes and reduction of adaptability. At the same time, a smooth, radiant, wrinkle-free complexion has been a global trend in cosmetology for many years, which results in more and more people, especially women, benefiting from new non-invasive anti-aging treatments. One of such treatments offered on the cosmetology market are treatments utilising RF radio waves. Therefore, the aim of this study was to assess the impact of a series of treatments utilising RF on the skin of the faces of women. Materials and methods: The analysis of the results was carried out by the examined person and by the authors of the project via a point scale of visual assessment of skin condition. The following facial skin parameters were analysed in the study: depth of wrinkles, elasticity, skin brightening and moisturising. Results and conclusions: The conducted own study proves the impact of treatments using RF radio waves on the skin of the face. The applied series of treatments caused a partial reduction of the most visible and deepest wrinkles, as well as improved elasticity, brightening and moisturising of the facial skin.